Correlation of Sonographic Morphologic Index and CA-125 in Predicting the Nature of Ovarian Tumor - Gusain, Poonam; Rawal, Suniti Joshi; Paudel, Sharma (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Ovarian tumor is a group of diseases that originates in the ovaries or in the related areas of the fallopian tubes and the peritoneum. Ovarian cancer causes more deaths than any other cancer of the female reproductive system. This study was undertaken to evaluate the efficacy of Sonographic Morphology Index (MI) and CA-125 levels in predicting malignancy in patients with ovarian tumors.Methods: This study was conducted between April 2016 and April 2017 in the Department of Obstetrics and Gynaecology and Radiology of Tribhuvan University Teaching Hospital. During this period,106 women with ovarian tumors fulfilling inclusion criteria were taken into the study. CA-125 levels measured and MI scoring was done. The diagnosis made with MI score and CA-125 score were then compared with histopathology report.Results: Among the 106 studied cases (N=106), 88 (83.01%) had benign and 18 (16.98%) had malignant ovarian tumors. Negative Predictive Value (NPV) and sensitivity of CA-125 for ovarian tumor was 94.10% and 77.77 % respectively with accuracy of 73.58%. Sensitivity and NPV of MI score was 100% with accuracy of 84.9% in predicting nature of ovarian tumors. Pearsonscorrelation coefficient was 0.216 which showed a positive correlation between MI and CA-125 in predicting nature of ovarian tumors.Conclusion: The Sonographic MI system is an accurate and simple method to differentiate a malignant tumor from a benign ovarian tumor. The accuracy of the Sonographic MI system improved when the serum CA-125 level was also considered along.